The Influence of Country of Origin, Brand Image, and Brand Trust on Brand Loyalty in Oppo Smartphone Users - Ardian Irfandani; Rohmat Dwi Jatmiko; R. Iqbal Robbie (Universitas Muhammadiyah Malang, 2021)
This study aims to determine the influence of the country of origin, brand image, and brand trust on brand loyalty partially. This study uses primary data collected by questionnaires. The data sample used is 120 respondents of Oppo smartphone users from the Faculty of Economics and Business, University of Muhammadiyah Malang. The sample collection technique is non-probability sampling with a purposive sampling method that provides certain criteria to the respondents. Respondents selected are active students of the Management, Accounting, and Development Economics study program class of 2017 who use smartphone Oppo released in 2017 to 2020. The data analysis technique used is multiple linear regression. The results of this study are 1) the variable country of origin has a significant effect on the variable brand loyalty, 2) the variable brand image has a significant effect on the variable brand loyalty, and 3) the variable brand trust has a significant effect on the variable brand loyalty.